Nucleated erythrocytes in blood smears of dogs undergoing chemotherapy. (25th June 2015) - Moretti, P.; Giordano, A.; Stefanello, D.; Ferrari, R.; Castellano, S.; Paltrinieri, S.
Abstract: The frequency of normoblastemia in dogs receiving chemotherapy is unknown. To provide this information, we calculated the percentage and number of nucleated erythrocytes (nRBCs) in blood of dogs treated for lymphoma ( n = 284), mast cell tumour ( n = 40) or carcinoma ( n = 46). Relative normoblastemia (>1 or >5%) and absolute normoblastemia (>0.1 or >0.4 × 10 3 µL −1 ) were found after administration of vincristine (49.3, 20.5, 42.5, 19.2%, respectively), carboplatin (37.0, 2.2, 34.8, 13.0%), cyclophosphamide (30.8, 7.7, 23.1, 7.7%), doxorubicin (25.0, 8.3, 21.7, 6.7%), vinblastine and prednisone (25.0; 5.0; 22.5; 7.5%). Absolute normoblastemia was very severe (>1.0 × 10 3 nRBC µL −1 ) after administration of vincristine (9.6%), doxorubicin (3.3%), vinblastine and prednisone (2.5%). Absolute normoblastemia negatively correlated with RBC counts ( P < 0.001) and positively ( P < 0.001) with reticulocyte and WBC counts, but correlation coefficients were low (−0.19, 0.37, 0.15). Vincristine, doxorubicin or vinblastine and prednisone may induce severe normoblastemia. This may increase WBC counts and mask neutropenia associated with chemotherapy.